Perioperative elafin for ischaemia-reperfusion injury during coronary artery bypass graft surgery: a randomised-controlled trial. Issue 20 (26th August 2015) - Alam, S R; Lewis, S C; Zamvar, V; Pessotto, R; Dweck, M R; Krishan, A; Goodman, K; Oatey, K; Harkess, R; Milne, L; Thomas, S; Mills, N M; et al.
Abstract : Background: Elafin is a potent endogenous neutrophil elastase inhibitor that protects against myocardial inflammation and injury in preclinical models of ischaemic-reperfusion injury. We investigated whether elafin could inhibit myocardial ischaemia-reperfusion injury induced during coronary artery bypass graft (CABG) surgery. Methods and results: In a randomised double-blind placebo-controlled parallel group clinical trial, 87 patients undergoing CABG surgery were randomised 1:1 to intravenous elafin 200 mg or saline placebo administered after induction of anaesthesia and prior to sternotomy. Myocardial injury was measured as cardiac troponin I release over 48 h (area under the curve (AUC)) and myocardial infarction identified with MRI. Postischaemic inflammation was measured by plasma markers including AUC high-sensitive C reactive protein (hs-CRP) and myeloperoxidase (MPO). Elafin infusion was safe and resulted in >3000-fold increase in plasma elafin concentrations and >50% inhibition of elastase activity in the first 24 h. This did not reduce myocardial injury over 48 h (ratio of geometric means (elafin/placebo) of AUC troponin I 0.74 (95% CI 0.47 to 1.15, p=0.18)) although post hoc analysis of the high-sensitive assay revealed lower troponin I concentrations at 6 h in elafin-treated patients (median 2.4 vs 4.1 μg/L, p=0.035). Elafin had no effect on myocardial infarction (elafin, 7/34 vs placebo, 5/35 patients) or on markers of inflammation: mean differences for AUC hs-CRP of 499 mg/L/48 h (95% CI −207 to 1205, p=0.16), and AUC MPO of 238 ng/mL/48 h (95% CI −235 to 711, p=0.320). Conclusions: There was no strong evidence that neutrophil elastase inhibition with a single-dose elafin treatment reduced myocardial injury and inflammation following CABG-induced ischaemia-reperfusion injury. Trial registration number: (EudraCT 2010-019527-58, ISRCTN82061264 ).